URGENSI PAI DALAM PEMBENTUKAN KEDISIPLINAN SISWA DI SMP IT BALIKPAPAN ISLAMIC SCHOOL - Rini, Hardiyanti; Yusuf, Iskandar (Cahaya Ilmu Bangsa Institute, 2025)
This study aims to see the urgency of PAI in the formation of student discipline at SMP IT Balikpapan Islamic School. This study uses a qualitative descriptive approach with data collection techniques in the form of observation, interviews, and documentation. The results of the study are 1. Islamic Religious Education has a very strategic role in forming the character and discipline of students at SMPITM BIS. PAI not only provides an understanding of religious values, but also instills moral principles that are an important foundation for the formation of a disciplined attitude. 2. The main challenge we face in implementing PAI to improve the discipline of grade VII students is the difference in background and parenting patterns that students have. 3. The role model of teachers and school staff is a key factor in forming student discipline. Students tend to imitate the behavior they see, not just what they hear. 4. The most effective method is an integrative approach, where PAI values ​​are not only taught in theory in class, but also practiced in various school activities. For example, through the tahsin, tahfidz, congregational prayer, and character building programs. Another approach we use is habituation, such as giving rewards and punishments that are in accordance with Islamic values. In addition, a personal approach is also very important, namely by building a good relationship between teachers and students so that students feel appreciated and more open to receiving advice. 5. Collaboration between schools and parents is very important in instilling student discipline. We always hold regular communication with parents through forums such as parenting day, parent-teacher meetings, and class communication groups. One of our flagship programs is